Enhanced Aerobic Sludge Granulation by Seeding Concentrated Activated Sludge with Ca‐Alginate Gel. (1st December 2017) - Sun, Can; Zhan, Hanhui; Wang, Liangjie
ABSTRACT: : The present study focuses on the effect of Ca‐alginate gel on aerobic sludge granulation. Three sequencing batch reactors (SBRs) seeded with different mixtures of Ca‐alginate gel and activated sludge with the fraction (weight/weight of dry biomass) of 0%, 5.5%, and 15.5%, respectively. The granulation time of 14 days was obtained with 5.5% additive, while 32 days were needed to adapt aerobic granules developed with 0% Ca‐alginate gel. Full granulation was achieved in the trial with 15.5% additive from the 20th day. Comparing with granules in reactor 1, the granules cultivated with Ca‐alginate gel exhibited attributes of much faster settling velocities, higher biomass retention, greater mechanical strength, and better nutrient‐removing capability. The alginate‐metal gel may be the structural polymer of aerobic granules and offer bacteria the inhabitancy and protection, which is beneficial to retain more biomass and improve the efficiency of wastewater treatment.